BRIONY’S GUILTY FEELING AND HER ATONEMENT IN IAN MCEWAN’S ATONEMENT (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
BRIONY’S GUILTY FEELING AND HER ATONEMENT IN IAN MCEWAN’S ATONEMENT Lailatul Fitriya English Literature Study Program, Faculty of Languages and Arts, Surabaya State University lailafitriya71@yahoo.co.id Drs. Much. Khoiri, M.Si English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Much_choiri@yahoo.com Abstrak Perasaan bersalah dan taubat adalah hal yang ditunjukkan oleh seseorang ketika mereka membuat kesalahan atau dosa. Ian McEwan adalah salah satu penulis yang menulis sebuah novel tentang perasaan bersalah dan taubat. Penelitian ini bertujuan untuk menggambarkan perasaan bersalah dan taubat dari karakter utama. Dengan menggunakan teori-teori yang relevan, studi ini menganalisis kutipan-kutipan dari dalam novel yang mewakili perasaan bersalah dan taubat sebagai sumber data. Hasil analisis menunjukkan bagaimana perasaan bersalah Briony yang menyebabkan dirinya sebagai karakter utama melakukan taubat, perasaan bersalah tersebut dapat digambarkan dalam tiga jenis. Pertama, perasaan bersalah Briony yang digambarkan ketika dia menyadari kesalahannya dan dia merasa bahwa dia melakukan hal yang salah. Kedua, perasaan bersalah Briony yang digambarkan ketika dia melakukan hal yang baik. Ketiga, digambarkan ketika dia membuat permintaan maaf dengan mengatakan kebenaran yang sesungguhnya. Setelah perasaan bersalah ketiga muncul, dia ingin mengadakan taubat atas kesalahan yang dilakukan. Berdasarkan semua perasaan bersalah dalam hidupnya, ia kemudian mencoba untuk bertaubat dengan membuat cerita fiksi antara Robbie dan Cecilia. Sebagai novelis, ia menulis sebuah fiksi yang memiliki cerita bahagia antara Robbie dan Cecilia, karena dia menyadari tentang rasa bersalahnya yang telah membuat Robbie dan Cecilia menderita sampai akhir hayat tanpa bisa memenuhi cinta mereka berdua. Kata kunci: Rasa bersalah dan taubat Abstract Guilty feeling and atonement are the thing which have been showed by the people when they make a guilt or sins. Ian McEwan is the one of the writers that wrote a novel about guilty and atonement. This study aimed to depict a guilty feeling and an atonement of the main character. By using relevant theories, the study analyses the data for example, quotation from the novel that represent guilty feeling. The result of analysis shows how Briony’s guilty feeling depicted in the atonement can be described in three kinds. First, Briony’s guilty feeling is depicted when she realized of her guilt and she felt that she did a wrong thing. Second, Briony’s guilty feeling depicted when she did a good thing. Third is depicted when she made an apology by telling the fact. After the third guilty feeling passed, she wanted to make atonement. Based on all her guilty feeling in her life, she then tried to make atonement by making a fiction of Robbie and Cecilia. As a novelist, she wrote a fiction that has happy ending between Robbie and Cecilia, because she realized about her guilt that has made Robbie and Cecilia get suffered to death without being able to fulfil their love. Key words: Guilty feeling and atonement INTRODUCTION As in a general world, there is something that is always different in each side, good and bad is opposite one. In those two actions, there are consequences that will automatically happen in our live. Such an aphorism said that "what are you planting it so shall you reap even though it was a bit". It has a meaning that if we are doing the good attitude we will get good response or if we are doing bad attitude the bad response will appear too. But, as a human being, we often done a bad attitude or guilt that makes suffer to the other one. Guilt is a cognitive or an emotional experience that occurs when a person realizes or believes accurately or not that he or she has compromised his or her own standards of conduct or has violated a moral standard, and bears significant responsibility for that violation. It is closely related to the concept of remorse. In a fairly thought, if someone doing a guilt action, he or she will feel guilty feelings. Guilty feeling is remorse caused by feeling responsible for some offense. It is analogously with the story which narrated by Ian McEwan in his novel Atonement that actually told about a guilty feelings and the atonement of someone. Seen from the morphological point of view, the word guilty which means “having done something illegal or being responsible for something bad that has happened” is derived from the word guilt which has meaning “the fact that somebody has done something illegal or responsibility for doing something wrong or for something bad that has happened”. According to Sigmund Freud, the guilty feelings may arise when individual violates some ideals or values of “superego” by responding the impulses from the “id”. It may be more accurate in Freudian theory to speak about a “guilty ego”. Historically, guilty feeling arises when individuals involved in illegal acts, such as Salzmann said "Historically, the concept of guilt has involved an act transgressing or breaking a law." (Salzmann, 1983 in John Banmen 1988:79) ". In this story, Briony as the main character feels that she was doing a guilt that makes her regret of her self in her life. Her sister “Cecilia” and “Robbie” could not get their love and they died before they could be reunited together and she wants to get atonement for her sin. Therefore, in this study wants to show how is the problem build because the guilty feeling. Some guilty that did by the main character which cause of another people had pain and how is the punishment that have done by the main character. Then author wants to describe more about how is Briony’s guilty feeling, causes of Briony’s atonement and what actually done in her life. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How is Briony’s guilty feeling depicted in Ian Mcewan’s Atonement? How does the guilty feeling causes Briony’s atonement in Ian Mcewan’s Atonement? This study will use two concept theories which are in line with the statement of the problems. The first problem is how Briony’s guilty feeling depicted in Ian Mcewan’s Atonemen. This statement will use the concept of guilty feeling. According to Narramore individual may feel guilty because the actual violation of the law of God (Real guilt) or for emotional maladjustment (Pseudo guilt). Freud also said that, guilty feeling is based on the internalization of the values ​​of the parents and the community. Guilty feeling begins when the children are afraid of punishment and loss of love old people when they violate social norms. According to Sigmund Freud, guilty feeling occur when the ego act, or even mean, to act contrary to contrary to moral norms superego (Freud, 2006: 67). Narramore said that the Guilty feeling is divided into two types they are, the real guilt and pseudo guilt. Real guilt, every person is usually attached to the tendency to sin or transgress the law of God. Feelings have done wrong and have been proven guilty of the offense for violating the law of God is what is usually called the real guilt. Then the second problem is how ow does the guilty feeling causes Briony’s atonement in Ian Mcewan’s Atonement. This statement will apply the concept of atonement. According to Narramore (1981: 106) expresses real feelings of guilt is actually from sin and guilt is the result of violations of the laws of God and refusal to acknowledge these sins. People who feel guilty because it brought on a fault or a sin, he suffered stress , anxiety and feelings of guilt . Realized it or not, every person in his will have a feeling of guilt. People who have repented even also experience feelings of sin and guilt realistic. So, in doing a wrong action, wrongdoer must deal with his guilt by making atonement, for example, by repentance and apology to the victim, and also by making reparation and penance. It is good for the victim to forgive a wrongdoer who has made some atonement, and that removes his guilt; but if the victim refuses to forgive despite substantial atonement, the wrongdoer's guilt disappears anyway. People have some responsibility to help others of the community to deal with their guilt, by encouraging them to apologize, and by helping them to make reparation but we are not guilty for the wrong acts of anyone else. RESEARCH METHOD Research methodology that used in this analysis here must be qualified as an applying in literary appreciation. In conducting the study, the descriptive qualitative method is applied and also uses a library research. The purpose of using the descriptive qualitative method is to obtain systematical description and accurate data which are dynamic, complex, and need very deep (Sugiyono, 2010: 399). The descriptive method of this study can be elaborated as below: Data and Sources of Data The data of this study used the Novel of Atonement, the eleventh book written by Ian McEwan and was published in 2001 as the main data in the analysis. Meanwhile, according to Arikunto in Afidah ( 2009: 27), the sources of data are grouped into three types. They are people, places, and papers. But, in this study the source of the data are obtained from the papers it is a novel by Ian McEwan as sources, in this case, mean that the data are obtained form of quotations, dialogues which indicate and represent aspect of slavery and the way it is expressed. Data Collection The method of collecting data, which is used in this study, is the library method. It does not use the statistic method. Library research used an approach in analyzing this study. That is why it is not served in numbering or table. The kind of library research here are intensive or closely reading to search quotations or phrases and to analyze literary element both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the ideas of analyzing. Data analysis The final part of research methods was data analysis. It presents some steps how to analyze the data. Some steps of how the data is analyzed will be described as follows: Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are three classifications is used to avoid the broad discussion. They are Briony’s behavior, Briony’s guilty, and Briony’s behavior causes her atonement. Describing Briony’s behavior characterization, which is stated from the quotations and statements by using theory of characterization to be applied to the data. Describing of guilty feeling. Quotations classified the guilty feeling that was done by main character in the novel. Revealing the atonement of the gulity. In this case,the quotations that are showed and indicated the reason of atonement that was done by the main character and showed how the atonement type of the main character. ANALYSIS The first section is about describtion of Briony’s guilty feeling. Briony’s guilty feeling appear when she was to be adult. She conscious that she have ever did a guilt to someone. When Briony in 13 years old, Briony witnesses a moment of sexual tension between Cecilia and Robbie from afar. she misinterprets the sexual act as rape and believes Robbie to be a "maniac". Later on at a family dinner party, attended by Briony's brother Leon and his friend Paul Marshall, it is discovered that the twins have run away and the dinner party breaks into teams to search for them. In the darkness, Briony discovers her cousin Lola, apparently being raped by an assailant she cannot clearly see. Lola is unable or unwilling to identify the attacker, but Briony decides to accuse Robbie and identifies him to the police as the rapist, claiming she has seen Robbie's face in the dark. Robbie is taken away to prison, with only Cecilia and his mother believing his protestations of innocence. From the part that was describe above, Briony was described as the young girl who is doing a wrong thing and really did a big guilt to Robbie. She did a crime to Robbie. She give a wrong witnesseth to the police.. ““She wanted the inspector to embrace her and comfort her and forgive her, however guiltless she was. But he would only look her and listen. It was him, I saw him, (McEwan, 2001:163). Although she actually knows, whose people that raped Lola, but she wants to Robbie whose became a subject of that crime to Robbie because she feel that Robbie is a man maniac that have to be punish. She told to the police that the ones of that criminal is Robbie “Robbie have been catched by two inspectors on Briony’s guilt of giving the wrong witnesseth”. (McEwan, 2001:173). What was Briony did is realy the wrong thing, she became a lier who give a wrong witnesseth. After wrongly accusing an innocent man of a horrible crime, Briony must live with the guilty. She realize that what she was done was something that made pain to someone else. Robbie cathed by the police, so he will entered to the jail. He will get a lot of pain in the jail, he should to responsible from the raped’s accusation and he would not have to meet Cecilia, his lover. He really suffered from the guilt or wrong witnesseth of Briony. Actually, Briony find a guilty feeling in her life because she did a sins or did something wrong to another. According to Sigmund Freud, the guilty feelings may arise when individual violates some ideals or values of “superego” by responding the impulses from the “id”. It may be more accurate in Freudian theory to speak about a “guilty ego”. Whereas, as mention by Salzmann in John Banmen in the previous chapter, guilty feeling arises when individuals involved in illegal acts (Banmen 1988:79). In this case, Briony’s Guilty feeling appear after she realize that she did a sins that is became a lier and did something wrong about give a wrong witnesseth to Robbie and causing him brought a lot of pain. That Briony’s guilty feeling was caused by doing sins. All off in the religious, did bad thing until made someone get suffer is one of sin and violation of the God that give an obligation to did good thing to someone else. Therefore, if have been seen by types of guilty feeling, Briony’s guilty feeling is the one of real guilty because she did something that violations of the God law. As mention by Narramor in previous chapter that the real guilty is guilty feeling because the actual violation of the law of God. What Briony did to Robbie is a guilt thing. Guilt that made someone getting suffer and injustice. In this case, Briony’s guilty feeling is the type of social guilt. Like mentioned by Cavanagh (quoted by Al-Fitr RA., 2005), Social guilt is a fault which is psychologically and physically will cause injustice to others . It should be understood that the social dimension of the system will shed light on the value of the individual on how to behave in particular that will help others and behave in a certain way that would harm others. Here, Briony really conscious about her guilt, the first Briony’s guilty feeling was depicted for desire to get an apology. Briony showed that she is really feeling guilt to Robbie , she is realized and feel anxiety about her wrong thing when she was a young, when she did not really thought about the pain that was happened into Robbie. Briony guilty feeling was realized when she was grow up becaming adult, she really found a guilty feeling in his life and actually she feel afraid for her bad and wrong thing. “She wanted the inspector to embrace her and comfort her and forgive her, however guiltless she was” (McEwan, 2001:163). After she told to the police about the wrong witnesseth, she feel afraid and anxiety. Like the stated of Narramore, expresses real feelings of guilty is actually from sin and guilt is the result of violations of the laws of God and refusal to acknowledge these sins. People who feel guilty because it brought on a fault or a sin , he suffered stress , anxiety and feelings of guilt (Naramore,1981: 106). Briony’s guilt to Robbie that cause Robbie catched by the police and entered to the jail. Robbie did not come back to Cecilia as his lover. He really disappointed with Briony’s guilt to him although it was happened in many years ago. Robbie’s experiences in the war. We follow Robbie on his retreat to Dunkirk. But, Briony’s guilty feeling was not stop with just feeling guilty and anxiety on her life. In this second part the guilty feeling of briony’s guilt also depicted. By the time World War II has started, Robbie has spent 2–3 years in prison. He is then released on the condition of enlistment in the army to fight in war. Cecilia has trained and become a nurse. She cuts off all contact with her family because of the part they took in sending Robbie to jail. Robbie and Cecilia have only been in contact by letter. Remorseful Briony has refused her place at Cambridge and instead is a trainee nurse in London. She has realised the full extent of her mistake, and decides it was Paul Marshall, Leon's friend, whom she saw raping Lola. Briony still writes, although she does not pursue it with the same recklessness as she did as a child. This part of the story is also the first time we get to experience Briony as just a normal girl. We get to follow her and a friend when they have a day off sitting in the sun in a park listening to a band playing, cheerfully talking and laughing. This event makes her into a living human being, a young girl spending time with her friend, relaxing and having fun. It gives Briony another dimension, she changes from rigid character caught up in her own world and her writing and emerges as a warm, bright, young girl just like any other 18-year-old. In the end the event makes Briony feel guilty that they had fun at all because when they return to the hospital a convoy of wounded soldiers has arrived. The fact that they were laughing in the sunlight when others were suffering makes her feel guilty, just like she probably feels guilty throughout her life for enjoying it when Cecilia and Robbie cannot enjoy their lives. In this parts, describe that Briony’s guilty feeling also depicted from the second parts of this novel. As a self punishment, Briony decides to give up all the luxuries of an upper-class life. No Cambridge, no fancy flat to live in, no traveling, no job at the ministry. Briony hopes that her duties as a nurse during the war will serve as some sort of penance towards her. Yet the cost of doing so, is a complete stripping of her identity--she fails to exist as "Briony"--with no will nor freedom to go back. Briony become a nurse to depicted her guilty feeling as describe in parts before. This was her student life now, these four years, this enveloping regime, and she had no will, no freedom to leave. She was abandoning herself to a life of strictures, rules, obedience, housework, and a constant fear of disapproval. She was one of a batch of probationers--there was intake every few months--and she had no identity beyond her badge.(McEwan,2001:260) Briony actually knows that her Sister really love to Robbie, but they could not get on together. She tried to do something good thing, may for get a penance. She tried to meet Robbie and Cecilia for a penance. How Briony get a penance or doing atonement will be explain letter in 3.2. The effort of Briony to get apologies, she won’t that the guilty feeling would continue haunt her forever in her life. Described with Robbie on his retreat to Dunkirk and all that happens to him and his companions on the way there. Cecilia, who of course occupies his mind far more than Briony does, has sent him a letter telling him that Briony wants to change her statement and make him free, not just from prison but from accusation. This gets him thinking of her and of her motive for lying and sending him to prison. His only explanation is that the feelings she had for him when she was younger were still there when she read his letter to Cecilia on that day five years ago when she accused him of a crime he did not commit. Here Briony guilty feeling is showed, she wants to change her statement and make him free, not just from prison but from accusation. She sent a letter to Cecilia as the type of her apology, Cecilia thougth that Briony wants to get a penance. Like she said in her letter, “ she’s saying that she wants to be useful in a partical way. But I get the impression she’s taken on nursing as a sort penance. She wants to come and see me and talk” (McEwan, 2001:199). Guilty feeling that was felt by Briony, made her to did a good thing. She became a nurse and wants to be useful, but actually that was the way to meet Cecilia and work in the Cecilia’s old hospital. After a crime that Briony did to Robbie Cecilia cut herself off from her family, “ she (Cecilia) would never speak to her parents, brother and sister again” (McEwan, 2001:192). It show that Cecilia really disappointed with Briony. Cecilia decided became a nurse far from her house. As told before about type of social guilt, this Briony’s guilt made Cecilia injustice. Therefore, Briony also decided to be nurse and hides her true self, the writer, behind the appearance of a nurse. Seen from the the psychoanalysis, what the Briony did is one of the way to get an apology from her guilt. Her guilty feeling is depicted when she really wants to meet Cecilia and Robbie to talk, admitted her wrong thing and to change the statement for Robbie to be free. Briony also change her life became a nurse to be useful in practical way, to found the penance. What Briony going to do is show that her guilty feeling is typically wants to covering her guilts with did a something good or usefull and tried to honest, admitted the real act that have been happened. According to Narramore, this type guilty feeling that had been showed by Briony is the guilty feeling Exemplary behavior. The examplary behavior is, when Individuals behave “friendly” and “nice” to cover her/his true feelings that happened to her/him from the guilty feeling (Naramore, 1981: 106). That was like Briony done to cover her true feeling, but actually she really in an guilty feeling with Cecilia and Robbie. Briony’s guilty feeling also change her life. Briony daydreams about being a famous writer, a name that is recognized throughout all of London for her magnificent ability at playwriting. In London, at the age of 18, she has been self-demoted to a slave, "a life of strictures, rules, obedience, housework, and a constant fear of disapproval." But what is even worse for her, is that she lives in a world where her name does not even exist. As a self punishment, Briony decides to give up all the luxuries of an upper-class life. No Cambridge, no fancy flat to live in, no traveling, no job at the ministry. Briony hopes that her duties as a nurse during the war will serve as some sort of penance towards her. Like mentioned by Narramore before about examplary behavior. Briony did not stop by did a good thing became a nurse to depicted his guilty. Briony tried to get an apology from Robbie and wants to meet Robbie and Cecilia. Here, she was ready to talk with Robbie and Cecilia who was actually did raped to lola in many years ago. Briony tried to find out the social justification from Robbie and Cecilia. She though may Robbie wants to give her an apology after she told the fact of her witnesseth. Briony met Robbie and Cecilia in Cecilia’s house. Briony said about what she is seing when that crime tragedy and whose person done a raped to lola in many years ago, although they were really disappointed and Robbie did not want to see Briony again. Like a quotation in the novel that showed Robbie ignore what Briony said, “ Briony was shaking her head and staring to speak, but Robbie ignore her and spoke over her” (McEwan, 2001:326) Its like open the past pain to Robbie, but Briony must to talk. Briony told that Paul Marshal was the criminal of raped. Briony stood too and said, “Old hardman was probably telling the truth. Danny was with him all that night”. Cecilia was about sheet of paper she had been writing on. Robbie had stoped in the bedroom doorway. Cecilia said “what do you meant by that? What are you saying?”. “It was Paul Marshall.” (McEwan, 2001:327) The explanation above described that Briony is not the only person who is guilty. Most obviously, Paul Marshall is guilty. Lola is guilty, too, in remaining silent about who attacked her. Lola finds in Briony's certainty a chance to escape the humiliation and difficulty of accusing Paul. Paul and Lola let Robbie bear the punishment for Paul's crime and are more culpable than Briony - she at least believes he is guilty while they know he is not. It is possible that Paul and Lola try to atone through their acts of charity, but theirs is a different story, not the one which Briony is intent on telling. Briony have to tell the fact about that crime to Robbie and Cecilia. All Briony did are the way to cover her guilty feeling and showed that she really wants to get an apology for her guilt. Like have been described before that Briony depicted her guilty feeling with a good thing again, she wants to responsible of her guilt. Still in agreement with Narramore said before about a type of guilty feeling, and types of Briony’s guilty feeling is Exemplary behavior. In This case Briony depicted her guilty feeling by admitted her guilty to Robbie and Cecilia and told the fact who actually did a crime to Lola. Briony have been told the fact to Robbie and Cecilia about who was raped Lola. It was make Robbie remembered a pain that he was felt because of the wrong Briony witnesseth. After Robbie get the penance of the Briony, Robbie wants that Briony give the confession to the trial and bring again Robbie’s reputation, but unfortunately all the evidences to blame Paul Marshall as the man who did a crime to Lola because Paul Marshall and Lola have been merried. Briony attends the wedding of her cousin Lola and Paul Marshall before finally visiting Cecilia. Robbie is on leave from the army and Briony meets him unexpectedly at her sister's. They both refuse to forgive Briony, who nonetheless tells them she will try and put things right. She promises to begin the legal procedures needed to exonerate Robbie, even though Paul Marshall will never be held responsible for his (supposed) crime because of his marriage to Lola, the victim. “ I want to kill him (Paul Marshal)” (McEwan, 2001:328) Robbie in a rage heard what Briony’s said about their wedding. In this case, Paul Marshall is guilty. Lola is guilty, too, in remaining silent about who attacked her. Paul and Lola let Robbie bear the punishment for Paul's crime. Kill Pul Marshall means that Robbie really disappointed because there was no way to blame him, because Lola will always cover for him from the police (trial). Briony felt tortured when she was seeing Robbie and Cecilia could not life happily. Now, there was no thing to help Robbie from his suffer, because Briony can give the evidence of the right and she could not blame Paul Marshall for gave Robbie’s reputation. In the end, Briony just could have to said sorry to Robbie and would letting his life. She spoke slowly. “I’m very sorry. I’ve caused you such terrible distress.” They continued to stare at her, and she repeated herself. “I’m very sorry.”[….] Robbie said softly, Just do all the things we’ve asked.” It was almost conciliatory, that ‘just’, but not quite, not yet.she said, “of Course”, and then turned and walked away [….] (McEwan, 2001:329) Briony guilty feeling have to desire to apology. She really wants to deal with her guilt with an apology and penance. As mentions by Narramore, People who have repented even also experience feelings of sin and guilt realistic . So, In doing a wrong action, wrongdoer must deal with his guilt by making atonement, for example, by repentance and apology to the victim, and (often also) by making reparation and penance (Narramore,1981: 106 ). Briony’s guilty feeling would deal by making an apology to Robbie and doing an atonement from the guilt, but that will explain in next part. Then, the second parts of this analysis will be describe of Briony’s guilty feeling causes her atonement. Focus on Briony’s atonement, she did an atonement after she did a guilt to someone. The Briony’s along journey with her guilty feeling is the parts to her get an atonement. Atonement here as the result of all Briony’s guilty feeling that have been described before. Briony wants Robbie and Cecilia forgive her by doing an atonement. Briony showed that she really did an atonement when she was on 77 years old or exactly in the end of this novel, after Briony realize about her guilty feeling that have been describe in 3.1. Briony’s guilty feeling that have been describe before delivered her to made an atonement. Briony remorseful for her guilt to Robbie and Cecilia, her guilty feeling that made another people get a suffer delivered her to do an atonement. After wrongly accusing an innocent man of a horrible crime, Briony must live with the guilty feeling. The fact that her actions condemned her sister’s true love to a life in prison made the feeling of betrayal all the worse. This betrayal was to live with Briony all her life and would dominate her hopeless journey to gain forgiveness that was never to be realized. “How guilt refined the methods of self-torture, threading the beads of detail into an eternal loop, a rosary to be fingered for a lifetime”, (McEwan, 2001:162) The quotation refers to a rosary which is a necklace of prayer beads, often used by Catholics when reciting Hail Mary. The Hail Mary prayer and a rosary are usually used during a request for repentance in which the person praying is feeling shame or remorse. That full of symbolism to show that Briony’s suffering is perpetual because there will never be a time that she does not feel an all-consuming regret for her actions. The only way Briony knows and thinks she can begin to atone for her sins is to attempt to cast off her guilt onto the pages of a novel. Despite the tragedy that in reality befell the young couple, Briony can use her writing to make Robbie and Cecilia survive the war and to be together at last. Briony did crime in the past to Robbie was the one of sin that have to get penance and atonement. What Briony going to do is the way for getting a forgiveness from Robbie. As mention by Narramore, Atonement is usually done After feeling a lot of sin , evil , wrong treatment and failed to meet the conditions ( Narramore, 1981). The first Briony’s guilty feeling is depicted by for desire to get an apology. Briony showed that she is really feeling guilt to Robbie , she is realized and feel anxiety about her wrong thing when she was a young, when she did not really thought about the pain that was happened into Robbie. The pain which happened between Robbie and Cecilia that they could not love life happily together cause Cause Briony’s atonement. After Robbie and Cecilia was dead without fulfill he love each other because of Briony’s guilt, Briony has spent her entire life writing drafts of this book as atonement for the crime she committed when she was young which changed the lives of people around her. Since Briony is both the author of the book and one of its characters this will reflect upon the story and the characterisations. This essay will focus on Briony and the descriptions made of her, both when the point of view is her own and when she describes herself from the other characters’ points of view. It will also take a close look at Briony as an author and how her writing develops through her life and reflects her own personality. Briony describe her atonement for all her guilty feeling when she was at the end of adulthood. Briony’s thought that It’s not death the nears for Briony at the end of the novel, but dementia - a state that promises to take her back to the childish confusion of the first part of the novel her character was so keen to conquer. She tries to convince herself that she “wasn’t distressed” about the onset of dementia. But the nearness of this condition - the disorder that it promises - makes it imperative to take stock of her life now and think about her legacy of atonement as a writer. “Lovers and their happy ends have been on my mind all night,” (McEwan, 2001:349). She narrates at the very end of the novel, “as into the sunset we sail. An unhappy inversion. It occurs to me that I have not travelled so very far after all, since I wrote my little play” Her completion of her last novel - with its fictional happy ending for Robbie and Cecilia, is her final act of atonement and order as an adult” (McEwan, 2001:349). Briony realize that her guilt make Robbie and Cecilia unhappily in their life until they dead, so by her novel she wants make a fiction that told happy ending for Robbie and Cecilia. The Second Briony’s guilty feeling is depicted in 3.1.2, that she became a nurse. Briony hopes that her duties as a nurse during the war will serve as some sort of penance towards her. Briony decided to get an atonement with her way as the writer again. Again and again to continue her wrinting. The third Brionys guilty feeling that have been describe in 3.1.3, told the fact to Robbie and Cecilia about who was raped Lola. After lying and ruining two young people’s lives, Briony seems to know even when she is older that her regret will last forever and that her sister will never forgive her, “Don’t worry. I won’t ever forgive you (McEwan, 2001:318). The last novel that she would made before she dementia as for her atonement to Robbie and Cecilia. Though the guilt caused by her selfishness would stay with her forever, there was one way in which it could have been slightly relieved, which is for Robbie and Cecilia to be reunited and live happily ever after. Since they never were able to be together, Briony wrote here sincerest apology in the story of Robbie and Cecilia’s reunion at the end of her novel. In religius theories the word Atonement “describes the setting ‘atone’ of those who have been estranged, and denotes the reconciliation of man to God. A rephrasing of the basic question Briony struggles with is this: How can I be rewarded my forgiveness if I am the one who gets to decide what happens? In other words, one cannot self-ascribe atonement. She can seek it, but is must be granted by the one who has been wronged or injured. Being author of the story places Briony in a bind because of her "absolute power to decide outcomes." She asks if she is not "also God?" meaning to the characters and episodes in her book. She is. As author she has the power to do anything to anyone or any situation. Recognizing this power, Briony concludes that there can be "no atonement for God or novelists," and only the attempt matters. . Briony’s wrote a novel is an attempt at Briony trying to find atonement for her sins. But when she herself is the author it is not an easy task: The problem these fifty-nine years has been this: how can a novelist achieve atonement when, with her absolute power of deciding outcomes, she is also God? There is no one, no entity or higher form that she can appeal to, or be reconciled with, or that can forgive her. (McEwan, 2001:350-351) In the end she writes the novel as atonement, not as a way for her to be forgiven. She does not walk the easy path and make herself the likable character that the reader will be fond of, identify with and easily forgive, nor does she excuse herself or her actions. Having the other characters forgive her in the novel was not an option either: “I gave them happiness, but I was not so self-serving as to let them forgive me.” (McEwan, 2001:351). In the last section of the novel Briony writes from the first person point of view telling the reader about events that occurred after the completion of the novel. The impression she makes then is quite different from the one she has made throughout the story. She probably has changed a great deal since she was 18 years old (young Briony) but the major most noticeable change is that she has finally become a likable character. She has the role of the old grandmother in the heart of a big family that all love her. Though she probably has changed a great deal there are parts of her that remain the same. Briony is suffering from a disease that will make her slowly lose her memory. Before this happens she makes sure all her business is in order; she finishes of the book, files and labels all the previous drafts and makes her “tidy finish” (McEwan, 2001:330). This sense for order has been with her throughout her life and is still a prominent part of who she is. Briony in 77 years old is an author to the fingertips; she has written books her whole life and the writing of this novel is a manifestation of all her skills. A truly interesting novel cannot just tell what happened, it must be skilfully narrated to capture the reader which Briony’s novel does from start to finish. She has abandoned the modernist approach of Briony and moved back towards the writer she was when she was younger: “It occurs to me that I have not travelled so very far after all, since I wrote my little play. Or rather, I’ve made a huge digression and doubled back to my starting place” (McEwan, 2001:349-350). She realised that the most important part of a novel is plot and a narrative pull in that plot; now she writes in the same way she did in her younger days but with much more refinement and finesse. In this, the last revision of the story, she adds a scene that did not really happen and that has not been part of the previous drafts; the scene where she meets Cecilia and Robbie again. In this scene Briony meets her sister and Robbie again and they have a chance to clear things up between them. It is a chance for Briony(at the end adult) to imagine what might have happened had they been able to meet again. She is not forgiven, that she cannot bring herself to become, but there is a mutual agreement between her and the two lovers and their parting is far less hostile than their meeting. During the meeting Cecilia says; Come Back the same way she did to bring Briony out of her bad dreams when she was little but this time it is to bring Robbie back from his bad dreams. It is a clear example of how Briony alienates herself from their world; having Cecilia use the same way of bringing back Robbie from his bad dreams as Briony remembers from her childhood but so decisively excluding herself from it. She is not allowed to enter their world, or she does not allow herself to enter it. This is part of the novel is a result of her travelling back to her starting place; the ending where the lovers get each other and live happily ever after, just like they always did in her childhood stories. Briony reveal sin the final section that both Robbie and Cecilia died before they could be reunited but she herself wonders “what sense or hope or satisfaction could a reader draw from such an account?” (McEwan, 2001:350). She no longer only writes an account of what happened but also writes a novel with her reader in mind. When … the novel is finally published, we will only exist as my inventions. Briony will be as much of a fantasy as the lovers who shared a bed in Balham and enraged their landlady. No one will care what events and which individuals were misinterpreted to make a novel. I know there’s always a certain kind of reader who will be compelled to ask, But what really happened? The answer is simple: the lovers survive and flourish. As long as there is a single copy, a solitary typescript of my final draft, then my spontaneous, fortuitous sister and her medical prince survive to love. (McEwan, 2001:350) What Briony describes is the power of the novel, to make a story alive and keep it alive. This passage, again, makes us aware of the fact that it is a novel we hold in our hands and the story in it stays alive through our copy of it and our reading of it. That is also a reason for her to give them a happy ending; to make a novel that the reader will want to read over and over. The scene where the lovers end up together serves another purposeas well; it is a climax in the story. It is an event to which the others build up and from which the action then falls. It helps the story follow the Freytag pyramid (Griffith 46) and once again it is a step back from the experimental writing of her youth to the simple telling of a story. What a Briony made for her atonement by writing a novel with the reunited Robbie and Cecilia in happily ending, actually it did not change a suffer which Robbie and Cecilia felt because her guilty. Its about the guilt between her and another people, and sins for God. Briony thougth, If the forgiveness could not give from Robbie and Cecilia, she must to have an atonement. Their story has become a fiction, but also an atonement and a tribute. As Briony says, “they would soon all be forgotten anyway, without the book, and then what difference would it make what 'really happened?”(McEwan,2001:371) As purpose by Robert that Forgiveness may be considered simply in terms of the person who forgives including forgiving themselves in terms of the person forgiven or in terms of the relationship between the forgiver and the person forgiven(Robert : 2001). In her story of her novel she made, she never tries to make herself a likable character that the readers will forgive even though it would have been so easy for her to do so. She has the skills to make the readers think what she wants them to but she chooses not to use them, the novel is atonement for her sins a way to, however little, make up for what she has done, having the reader like her and forgive her is not part of that atonement. She does not want to be a pleasant character, she prefers to be the disagreeable character who is, unlike her early creations, neither good nor bad and who can be judged independently of the reader’s personal likes and dislikes. That is her Atonement and her life’s work. Her completion of her last novel - with its fictional happy ending for Robbie and Cecilia, is her final act of atonement and order as an adult. CONCLUSION As a conclusion of this study, this study would like to give the readers an overall view what she has discussed in previous chapters. Based on the analysis, there are two main conclisions : The First conclusion is concern with the analysis about Briony’s guilty feeling. Briony’s guilty feeling showed after she did a sin to Robbie and Cecilia. Briony doing a crime to Robbie that makes suffer in Robbie’s life until the end. Briony make of robbie’s pain because he cannot fulfil and reunite her love with her lover Cecilia. In this analysis Briony’s guilty feeling depicted in three kinds. First, Briony’s guilty feeling showed when she was realized of her guilt and she feel that she is did a wrong thing. Briony showed that she is really did a guilt to Robbie, she is realized and feel anxiety about her wrong thing when she was a young, when she did not really thought about the pain that was happened into Robbie. Second, Briony’s guilty feeling by became doing a good thing to cover her guilty. As a self punishment, Briony decides to give up all the luxuries of an upper-class life. She becomes a nurse in world war. Briony hopes that her duties as a nurse during the war will serve as some sort of penance towards her. Third is she made an apology by telling the fact. Briony tried to get an apology from Robbie and wants to meet Robbie and Cecilia. Here, she was ready to talk with Robbie and Cecilia who was actually did raped to lola in many years ago. Briony tried to find out the social justification from Robbie and Cecilia. So, in this part found that Briony’s guilty feeling depicted by three actions. The second conclusion is about atonement of Briony causes her guilty feeling. After the guilty feeling was depicted by Briony in jurney of her life, finally she wants to make atonement from her guilt. Briony's writing of the novel again and again is her act of atonement for her crime. The false accusation wrecks the lives of Robbie and Cecilia, and for this Briony faces a lifetime of guilt. Delivered from her all guilty feeling in her life she try to make an atonement by made a fiction of Robbie an Cecilia. As a novelist, she wrote a fiction that has happy ending between Robbie and Cecilia, because she realized about her guilt that has made Robbie and Cecilia get suffered to death without being able to fulfil their love. However, their story has become a fiction, but also atonement and a tribute. REFERENCES Afidah, Nurul. (2009). Standard of Javanese politeness: The use of Javanese Speech Levels by Islamic Preaches. Unpublished. S1of State University of Surabaya Baumeister, Roy F. (1994). Guilt: An Interpersonal Approach. New York: American Psychological Association, Inc. (p.243-267) Childs, Peter, ed. The Fiction of Ian McEwan: A reader’s guide to essential criticism. Basingstoke: Palgrave Macmillan, 2006. Cryder E. Cynthia, Springer Stephen (2012), dkk. Guilty Feelings, Targeted Actions (p.607). Pers Soc Psychol bull Finney, Brian. “Briony's stand against Oblivion: the making of fiction in Ian McEwan's Atonement.” Journal of Modern Literature27.3(Winter2004): p68. Freud, Sigmund. (2006). A General Introduction To Psychoanalysis. Yogyakarta: Pustaka Pelajar Griffith, Kelley .(2006). Writing Essays about Literature: A Guide and Style Sheet. Boston, MA: Thomson Wadsworth. McEwan, Ian. ( 2001). Atonement. New York : A division of Random House, Inc. Strickland, Bonnie R. (2001). Encyclopedia of Psychology 2nd ed. Ed. Gale Group, Inc. (http://www eNotes.com, accessed on 5 January 2014) Sugiyono. (2010). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta, CV. Webster, Richard. (1996). Why Freud was wrong: sin, science and psychoanalysis. London: Harper Collins Internet Sources : http://www.apadivisions.org/division-39/publications/reviews/guilt.aspx (Accessed on 5 Februari 2014) http://www.yorku.ca/dcarveth/guilt.html. (Accessed on 5 Februari 2014) http://www.gradesaver.com/atonement/study-guide/quotes/. (Access on 5 Februari 2014) http://ayussoulimage.blogspot.com/2012/03/teori-rasa-bersalah.html. (Accessed on 18 Februari) http://vishakadharma.wordpress.com/2011/03/01/rasa-bersalah/ (Accessed on 1 Maret 2014)